TAX HARMONIZATION ASEAN MELALUI ASEAN TAX FORUM -PEMBELAJARAN DARI PROSES TAX HARMONIZATION UNI EROPA- - Suska, Suska; Effendi, Yuventus (Jurnal Kajian Ekonomi dan Keuangan, 2011)
ASEAN Tax Forum was established in the ASEAN Minister of Finance meeting in Bali April 2011. The forum consists of tax authority among ASEAN countries intended for exchange of information on the tax regime and instruments among Member States as well as to work on the issues of avoidance of double taxation and addressing withholding tax to further support the building of a competitive ASEAN Economic Community. The tax harmonization process among member states of ASEAN needs several stages to be taken. Tax Treaty as the step to eliminate the double taxation still not implemented by all ASEAN members. Tax rate particularly corporate tax rate is varying among countries. Learning the lesson from European Union, the direction of tax harmonization is to establish the common tax base while tax rate still differentiate among member states.